Rancang Bangun Alat Pengering Bawang Merah Berbasis Mikrokontroler - Safitri, Habibi; Simorangkir, Rivaldo Juniper Bertua (Universitas Harapan Medan, 2024)
Shallots exhibit heightened sensitivity to temperature and humidity compared to other onion varieties. Extreme climate change poses significant challenges for shallot farmers, leading to substantial losses. Adverse climatic conditions negatively impact the drying process, hampering its effectiveness. To address these issues, technological advancements offer opportunities for shallot farmers to optimize time, energy, and space utilization. Leveraging microcontroller technology enables the development of an efficient drying system for shallots. The utilization of the DHT11 Sensor technology proves highly advantageous in achieving quick and efficient drying of shallots. Various electronic devices and components, such as Arduino Uno, Stepdown, DHT11 Sensor, Heater, Rotary Encoder, Driver Relay, LCD, and DC Fan, are carefully integrated to construct the Onion Dryer. This innovative tool not only enhances the efficiency of the shallot drying process but also provides convenience for home-based shallot farmers. Consequently, the Onion Dryer plays a pivotal role in assisting farmers in maximizing crop yield, improving quality, and enhancing overall productivity. Moreover, the tool offers user-friendly operation, ensuring ease of use.